2005
DOI: 10.1111/j.1600-0765.2005.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of scaling and root planing versus modified Widman flap on nitric oxide synthase and arginase activity in patients with chronic periodontitis

Abstract: This study was the first report of evaluating the involvement of the arginine-NO pathway in chronic periodontitis and this might be considered to be of value in understanding the periodontal disease mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 24 publications
3
23
2
2
Order By: Relevance
“…This result is in agreement with the study by Gullu et al [56] who reported a reduction in the iNOS expression and number of inflammatory cells 2 months after non-surgical therapy. There was also an increase in the enzyme arginase activity following scaling and root planing.…”
Section: Latha Et Alsupporting
confidence: 83%
See 1 more Smart Citation
“…This result is in agreement with the study by Gullu et al [56] who reported a reduction in the iNOS expression and number of inflammatory cells 2 months after non-surgical therapy. There was also an increase in the enzyme arginase activity following scaling and root planing.…”
Section: Latha Et Alsupporting
confidence: 83%
“…In the study by Gullu et al [56], the authors reported that modified Widman flap surgery was more effective in lowering the count of iNOS expressing cells compared to SRP. Since all the patients in our study had moderate to severe periodontitis, non-surgical therapy was not very effective in reducing the level of NO.…”
Section: Latha Et Almentioning
confidence: 99%
“…iNOS activity was reported to increase in ligatureinduced periodontitis [27], experimental periodontitis [30], and chronic periodontitis [20,26,31]. Higher levels of iNOS expression were observed in chronic periodontitis tissues than in clinically healthy gingival tissues [20,23,26,27,31] and a previous study of ours showed that iNOS increased in the gingival tissue of aggressive periodontitis patients (unpublished data). In various animal models iNOS was susceptible to infections by a variety of pathogens [32][33][34][35].…”
Section: Introductionmentioning
confidence: 70%
“…NO has been implicated in the pathogenesis of apical infection [45], periapical granulomas [46], and inflamed human dental pulp [47]. Increased iNOS expression in gingiva was shown in periodontitis [20,22,26,28,31], ligature-induced periodontitis [27], experimental periodontitis [30,46], inflamed gingiva [23], localized aggressive periodontitis [21], and recently by our group in aggressive periodontitis (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation